Articulation of Balance - Erisman, Graham (East Carolina University, 2012)
This is my report on my creative research. It is supplementary to my thesis exhibition of works of sculpture, images of which are included in this report. These sculptures explore the idea of balance through articulation of focus. The idea of balance is expressed as a state of mind, as well as a visual equilibrium. My work embodies this concept through the use of color, geometric abstract forms and the use of permanent material.
Keywords: Fine arts; Aluminum; Casting; Enamel; Fabrication; Sculpture; Aluminum sculpture